Schistosomiasis Control in Nigeria: Moving Round the Circle? - Oyetunde T. Oyeyemi (Ubiquity Press, 2020)
Background: Schistosomiasis has continued to plague low-resource areas of the Nigerian population. Mass drug administration (MDA) has been the only adopted interventional program for decades. However, it appears this effort does not culminate in transmission and morbidity reduction. Purpose: To highlight the current situation of schistosomiasis in Nigeria, why MDA alone cannot achieve the expected result, identify research needs, and promotion of integrated control approach for schistosomiasis. Method: A viewpoint based on practices, research findings, and personal and professional experience in the field of schistosomiasis control. Conclusion: This viewpoint strongly advocates a commitment to the integrated control approach through the development of robust schistosomiasis control policy for the country. It stressed the need for research priorities in neglected areas of schistosomiasis that are germane for control of the disease. The government's willpower to implement important recommendations from research outcomes is important to achieve success.